A Very Unusual Presentation of Metastatic Colon Cancer. (23rd June 2011) - Fahrtash, Farzan; Chan, David; Colebatch, Andrew; Rutovitz, Joseph
Abstract : This case highlights two very rare complications of metastatic colorectal carcinoma. It describes a 59 year old female with both cutaneous and endometrial metastases from colorectal carcinoma. While both of these presentations are very unusual, they highlight the need to be vigilant about the detection of metastatic complications during follow up.